Angiogenin mutations in Hungarian patients with amyotrophic lateral sclerosis: Clinical, genetic, computational, and functional analyses. Issue 6 (25th April 2019) - Tripolszki, Kornélia; Danis, Judit; Padhi, Aditya K.; Gomes, James; Bozó, Renáta; Nagy, Zsófia F.; Nagy, Dóra; Klivényi, Péter; Engelhardt, József I.; Széll, Márta
Abstract: Introduction: Mutations in the angiogenin ( ANG ) gene are known to be associated with both familial and sporadic amyotrophic lateral sclerosis (ALS). The majority of disease‐causing mutations of ANG result in loss of either ribonucleolytic activity, nuclear translocation activity or both. Methods: We sequenced ANG gene from a total of 136 sporadic ALS patients and 112 healthy controls of Hungarian origin. To elucidate the role of the R33W mutation in the disease mechanism, computational, and functional analyses were performed. Results: Mutation screening revealed a mutation located in the signal peptide (M‐24I) and two mutations that affect the mature protein (R33W, V103I). The R33W mutation, which has not been previously detected in ALS patients, affects the key amino acid of the nuclear translocation signal of the ANG protein. Molecular dynamics simulations suggested that the R33W mutation results in partial loss of ribonucleolytic activity and reduced nuclear translocation activity. The ribonucleolytic assay and nuclear translocation assay of the R33W ANG protein confirmed the molecular dynamics results. Conclusions: In the Hungarian ALS population, the observed frequency of ANG mutations was 2.9%, which is higher than previously reported for sporadic cohorts. The evidence from computational and functional analyses support the deleterious effect of the novel R33W variant detected in this study. Abstract : Three angiogenin (ANG) mutations (M‐24I, R33W, V103I) were detected The R33W mutation affects the nuclear translocation signal of the ANG protein R33W results in partial loss of ribonucleolytic and nuclear translocation activity.